2009
DOI: 10.1377/hlthaff.28.1.64
|View full text |Cite
|
Sign up to set email alerts
|

Confronting The Growing Burden Of Chronic Disease: Can The U.S. Health Care Workforce Do The Job?

Abstract: The U.S. chronic illness burden is increasing and is felt more strongly in minority and low-income populations: in 2005, 133 million Americans had at least one chronic condition. Prevention and management of chronic disease are best performed by multidisciplinary teams in primary care and public health. However, the future health care workforce is not projected to include an appropriate mix of personnel capable of staffing such teams. To prepare for the growing chronic disease burden, a larger interdisciplinar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
348
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 492 publications
(354 citation statements)
references
References 28 publications
5
348
0
1
Order By: Relevance
“…40,41 Thomas Bodenheimer and coauthors have observed that the management of the growing burden of chronic disease will require multidisciplinary teams. 42 We believe that specialists will be a key component of such care delivery teams and that their roles will be clearly defined as part of evidence-based care plans. Failure to train sufficient numbers of specialists could exacerbate already long wait times, reduce access to care for some of the nation's most vulnerable patients, and reduce patients' quality of life.…”
Section: Resultsmentioning
confidence: 99%
“…40,41 Thomas Bodenheimer and coauthors have observed that the management of the growing burden of chronic disease will require multidisciplinary teams. 42 We believe that specialists will be a key component of such care delivery teams and that their roles will be clearly defined as part of evidence-based care plans. Failure to train sufficient numbers of specialists could exacerbate already long wait times, reduce access to care for some of the nation's most vulnerable patients, and reduce patients' quality of life.…”
Section: Resultsmentioning
confidence: 99%
“…Thomas Bodenheimer and colleagues 27 have contended that multidisciplinary teams are necessary for consistently good chronic care and that payment reform is critical for the sustainability of such teams. In a physician group practice, pharmacists can optimize medication use, improve care, and reduce costs.…”
Section: Payment Reform Strategiesmentioning
confidence: 99%
“…(1) The vast number of published research articles dealing with the wide variety of telemedicine applications and the need to reach a conclusion regarding the available evidence render an all-inclusive approach rather impractical. More important is that a voluminous report may not add a commensurate amount of information that would alter the conclusions reached by a focused approach.…”
Section: Introduction and Overviewmentioning
confidence: 99%